2021
DOI: 10.1109/access.2021.3090918
|View full text |Cite
|
Sign up to set email alerts
|

Gradient Descent Effects on Differential Neural Architecture Search: A Survey

Abstract: Gradient Descent, an effective way to search for the local minimum of a function, can minimize training and validation loss of neural architectures and also be incited in an appropriate order to decrease the searching cost of neural architecture search. In recent trends, the neural architecture search (NAS) is enormously used to construct an automatic architecture for a specific task. Mostly well-performed neural architecture search methods have adopted reinforcement learning, evolutionary algorithms, or gradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 31 publications
0
11
0
2
Order By: Relevance
“…Liang et al [ 34 ] observed performance collapse as the number of epochs of DARTS increased, and found that this was a result of overfitting due to the number of skip-connections that increased with epochs. They solved the performance collapse problem through DARTS+ [ 34 ], which applied the ‘early stopping’ technique, based on the research results that important connections and significant changes were determined in the early phase of training [ 49 , 50 , 51 ]. Chu et al proposed Fair-DARTS [ 35 ], which applied independence of each operation’s architectural weight to solve the performance collapse problem caused by skip-connection, and eliminated the unfair advantage.…”
Section: Neural Architecture Searchmentioning
confidence: 99%
“…Liang et al [ 34 ] observed performance collapse as the number of epochs of DARTS increased, and found that this was a result of overfitting due to the number of skip-connections that increased with epochs. They solved the performance collapse problem through DARTS+ [ 34 ], which applied the ‘early stopping’ technique, based on the research results that important connections and significant changes were determined in the early phase of training [ 49 , 50 , 51 ]. Chu et al proposed Fair-DARTS [ 35 ], which applied independence of each operation’s architectural weight to solve the performance collapse problem caused by skip-connection, and eliminated the unfair advantage.…”
Section: Neural Architecture Searchmentioning
confidence: 99%
“…According to the chain rule, the backpropagation algorithm uses the error between the expected and the actual output as the backpropagation, and uses the gradient descent method to adjust the network parameters to promote the error to develop in the direction of smaller [ 31 , 32 , 33 ]. The principle of the gradient descent algorithm is to find the extreme point of the objective function , which is the point where the derivative .…”
Section: Fpga Design Of Bp Neural Network Pid Algorithmmentioning
confidence: 99%
“…The search strategy specifies the algorithm used to search for the optimal architecture. These algorithms include: random search [27], Bayesian optimization [28], evolutionary algorithms [26], reinforcement learning [29], and gradient-based algorithms [30]. Among them, Google's reinforcement learning search method was an earlier exploration in 2017.…”
Section: Nas Problem Black Box Modelingmentioning
confidence: 99%